Burzū-nāma : Bakhsh-i kuhan - Kawsaj, Shams al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Firdawsī's (d. 411/1020) Shāh-nāma , this famous epic poem in celebration of the history of the kings and dynasties of Persia, was not written in a void. Indeed, before him there had been other epic works in Persian, more or less similar to it, by authors otherwise unknown, and now lost: by Masʿūdī Marwazī (before 355/966), by Abu ʼl-Muʾayyad Balkhī (before 352/963), by Abū ʿAlī Balkhī (before 390/1000), and the Shāh-nāma-yi Abū Manṣūrī (346/947). It has been said that Firdawsī may have taken some of his inspiration from this latter work. After Firdawsī, others wrote similar works, in imitation of him: Asadī Ṭūsī's Garshāsp-nāma (completed in 458/1066) and Īrānshāh b. Abi ʼl-Khayr's Bahman-nāma (501/1107-08) are just two examples of this. The present work by Shams al-Dīn Kawsaj (8th/14th century) is another epic poem in Firdawsī's style. The add-on found in some manuscripts, by a later author of lesser talent, is not included here.